Electoral intervention during the restoration in the Valencia province (1876-1923) - Martínez Relanzón, Alejandro (Hispania Nova, 2020)
It is well-known that many Spanish historians believe that the elections during the Restoration period were just a mere formality in which results were previously arranged upon by a dominant elite assisted by corrupted local notables. Nevertheless, these conclusions lack an in-depth analysis of the sources and have been based on extreme criticism rather than on strong evidence. The question that arises is this: did the Spanish governments of the time really determine elections through manipulation of the final results? With intensive study of unpublished documents from the archives of the minister of Internal Affairs and local governors in the Valencia province, the author attempts to reopen a debate about whether the governmental intervention determined electoral outcomes in Spain between 1876 and 1923.
Keywords: Restoration; governmental intervention; elections; vote-rigging